Original Programming Characteristics That Cause Subscription Video on Demand (SVoD) Subscription Behavior in Indonesia - Josephine Natalie (Return : Study of Management, Economic and Bussines, 2023)
This study aims to explore the characteristics of original content that can trigger Subscription Video on Demand (SVoD) subscriptions in Indonesia, identify factors that influence the desire to subscribe or unsubscribe from SVoD, and analyze factors that have no effect on the desire to subscribe to SVoD in Indonesia. This study adopted a grounded theory approach and involved 16 informants from Indonesia as research samples. The results showed that the main characteristics of original content that can increase subscription intent or trigger SVoD subscriptions include country of origin, type of impression, genre, feelings evoked, stories that are close to the audience's life, provide insight or knowledge, and quality. Conversely, shows whose content is limited to a region, has story content that is too heavy, spoilers that have been widely circulated, open endings, and an incomplete catalog of SVoD content are characteristics that are not able to trigger someone to subscribe to SVoD. In addition, the original language in the original content produced and the popularity of impressions on the internet also did not have a significant effect in triggering SVoD subscriptions. Other external strategies and factors that can prevent SVoD subscription cancellations and increase SVoD subscriber numbers involve promoting compelling original content synopses, increasing review activities and public relations marketing activities when releasing new original content in exchange for recommendations, and increasing indirect anti-piracy campaigns. This study provides valuable insights on how to increase SVoD subscriptions through the characteristics of original content and external factors influencing subscription behavior in Indonesia.